Plate 12: Cinchona bark - Wills, George S. V. (A Manual of Vegetable Materia Medica, 1886)
Illustrations printed in color of two varieties of cinchona bark. No. 109 is Cinchona Flavae cortex or yellow cinchona bark and No. 111 is Cinchonae Carthagenae cortex or Carthagena bark. This manual identifies plants used for medicinal purposes. The focus is on plants that can be acquired through commerce in Britain and are illustrated as they would have been imported and bought, for example the opium is illustrated as a processed capsule wrapped in a poppy leaf instead of the poppy plant itself. Authored by George Sampson Valentine Wills (1849-1932). Wills was the founder and Director of the Westminster College of Chemistry and Pharmacy in London. The school was established to train druggists for examinations by the Pharmaceutical Society of Great Britain, the regulating body established in 1841.
Keywords: Botany, Medical; Medicinal plants; Materia medica, Vegetable; Cinchona--Therapeutic use